Strickberger's evolution - Hall, Brian K. (Brian Keith), 1941-; Hallgrimsson, Benedikt; Strickberger, Monroe W. (Burlington, Mass. : Jones & Bartlett Learning, 2014)
The fifth Edition of Strickberger's Evolution is updated with the latest data and updates from the field. The authors took care to carefully modify the chapter order in an effort to provide a more clear and student-friendly presentation of course material. The original scope and theme of this popular text remains, as it continues to present an overview of prevailing evidence and theories about evolution by discussing how the world and its organisms arose and changed over time. New boxed features concentrating on modern and exciting research in the field are included throughout the text. New and Key Features of the Fifth Edition - New Full color design and art program - Maintains the student-friendly engaging writing-style for which it is known - A reorganized chapter order provides a more clear and accessible presentation of course material. - Chapters on the evolution of biodiversity are now found on the text's website. - Access to the companion website is included with every new copy of the text. - New boxed features highlight new and exciting research in the field.
1. Intellectual origins of the theory of biological evolution -- 2. Species and their relationships -- 3. Similarity and patterns of evolution -- 4. Universe and earth arise -- 5. The atmosphere, rocks and continents -- 6. Origin of the molecules of life -- 7. Molecules, membranes, and protocells -- 8. The first cells and organisms arose 3.5 bya -- 9. Eukaryotic organelles, genes, and organisms arose 1.8 bya -- 10. Voyages of discovery, natural selection and evolution -- 11. The theory of evolution by natural selection -- 12. Mendel, inheritance, and a theory of heredity -- 13. Genes, environment, and inheritance -- 14. Types of natural selection -- 15. Natural selection, phenotypes and genotypes -- 16. Chromosomes and genomes as sources of individual variation -- 17. Mutations and gene regulation as sources of individual variation -- 18. Genetic variation in populations -- 19. Dems, gene flow, and genetic drift -- 20. Competition, predation, and population biology -- 21. Coevolution -- 22. Phenotypic, plasticity and sympatric speculation -- 23. Allopatric speciation and hybridization -- 24. Mass extinctions, opportunities, and adaptive radiations -- 25. Human origins -- 26. Cultural and social evolution -- 27. Human influences on evolution -- 28. Culture, religion, and evolution.
Includes bibliographical references and index.
Keywords: Evolution (Biology).